Implementation of P5 through paper recycling in optimizing a sustainable lifestyle (case study at SDN Sukabumi Selatan 06 Pagi) - Hasanah, Suci Rahmadina; Suprianto, Oki; Robiansyah, Firman (International Conference on Education in Primary and Early Childhood, Marine, Computer Information, and Logistics, 2025)
Education in Indonesia has certainly undergone changes along with the increasingly dynamic development of the times, one of which is the implementation of the Independent Curriculum which emphasizes strengthening character through the Pancasila Student Profile Strengthening Project (P5), especially the theme of sustainable lifestyle. This study aims to analyze the implementation of P5 through the recycling of used paper materials in optimizing a sustainable lifestyle, with a focus on grade 5 B SDN Sukabumi Selatan 06 Pagi. The approach used is qualitative with a case study method. Data collected through observations, interviews and supporting documentation. The results of the study show that P5 activities are carried out through planning, implementation and involving cooperation between students, teachers, and parents. This activity not only teaches about the importance of protecting the environment, but also develops students’ character, such as cooperation, responsibility and creativity. Although there are challenges in the technique of the manufacturing process and group dynamics. Efforts to overcome challenges are carried out with technical guidance, division of tasks and coordination with parents. Thus, the implementation of P5 through the recycling of used paper materials can teach students to implement a sustainable lifestyle and strengthen the Pancasila Student Profile, especially caring for the environment.